Recent Advances of Individual BODIPY and BODIPY-Based Functional Materials in Medical Diagnostics and Treatment; Current Medicinal Chemistry; Vol. 24, iss. 25 - Marfin Yu. S. Yuriy; Solomonov A. V. Alexey; Timin A. S. Aleksandr Sergeevich; Rumyantsev E. V. Evgeniy (2017, 2017)
Title screen